2021
DOI: 10.3390/ph14050404
|View full text |Cite
|
Sign up to set email alerts
|

The Repurposing of Acetylsalicylic Acid as a Photosensitiser to Inactivate the Growth of Cryptococcal Cells

Abstract: Photodynamic treatment (PDT) is often successful when used against aerobic microbes, given their natural susceptibility to oxidative damage. To this end, the current study aimed to explore the photodynamic action of acetylsalicylic acid (ASA; aspirin, which is commonly used to treat non-infectious ailments), when administered to respiring cryptococcal cells. The treatment of cryptococcal cells, i.e., exposure to 0.5 or 1 mM of ASA in the presence of ultraviolet light (UVL) for 10 min, resulted in a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Moreover, care should be taken to prevent continuous photoreaction by keeping patients away from sources of UVC, as this radiation is damaging. To remedy this, treatment could be administered in the presence of a molecule that could modify how skin epithelial cells receive UV radiation [33]. Fortunately, UVC radiation from the sun is filtered by the atmosphere and, therefore, does not reach the earth's surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, care should be taken to prevent continuous photoreaction by keeping patients away from sources of UVC, as this radiation is damaging. To remedy this, treatment could be administered in the presence of a molecule that could modify how skin epithelial cells receive UV radiation [33]. Fortunately, UVC radiation from the sun is filtered by the atmosphere and, therefore, does not reach the earth's surface.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the idea of repurposing PQ is not foreign, as it has successfully been shown to control the growth of Pneumocystis jirovecii [31,32]. It is, therefore, theorized that PDT would be successful when used against aerobic microbes, similarly to Plasmodium and Pneumocystis jirovecii, given their natural susceptibility to oxidative damage [19,33].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to Cryptococcus spp., ASA has been evaluated as an alternative drug to control cell growth. An in vitro study on ten Cryptococcus strains demonstrated that ASA acts in synergy with fluconazole and amphotericin B in enhancing macrophage-mediated phagocytosis, killing cryptococcal cells and inhibiting cellular growth [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cryptococcus neoformans is also an opportunistic yeast pathogen causing cryptococcus, especially in the immune-compromised patients; around 73% of 223,100 annual cases of cryptococcal meningitis are diagnosed in sub-Saharan Africa with a 75% mortality rate [ 24 ]. Since photodynamic treatment (PDT) is a method of curing aerobic microbes susceptible to oxidative damage [ 25 ], Ogundeji et al [ 24 ] investigated the photodynamic activity of acetylsalicylic acid (ASA; aspirin) against respiring cryptococcal cells. Cryptococcal cells were exposed to 0.5 or 1 mM of ASA with ultraviolet light (UVL) for 10 min, which resulted in a significant reduction in the fungal growth compared to the non-treated control cells.…”
mentioning
confidence: 99%